2010
DOI: 10.1152/japplphysiol.01082.2009
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin and milrinone by aerosolization improve pulmonary hemodynamics in newborn lambs with experimental pulmonary hypertension

Abstract: Aerosolized prostacyclin (PGI2) produces selective pulmonary vasodilation in patients with pulmonary hypertension (PH). The response to PGI2 may be increased by phosphodiesterase type 3 inhibitors such as milrinone. We studied the dose response effects of aerosolized PGI2 and aerosolized milrinone both alone and in combination on pulmonary and systemic hemodynamics in newborn lambs with Nomega-nitro-L-arginine methyl ester (L-NAME)-induced PH. We hypothesized that coaerosolization of PGI2 with milrinone would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…36 Therefore, future preventive or therapeutic strategies in PH and RV failure should consider combining therapies that would target multiple sites of action as previously reported. 10,18,24,55 In summary, in high-risk cardiac surgical patients, iMil has favourable hemodynamic effect, no systemic hypotension, and is associated with an increased CO with a modest overall reduction in SPAP. Reduction in RV afterload after iMil can vary amongst patients and can be explained by variable PK/PD relationships.…”
Section: Discussionmentioning
confidence: 90%
“…36 Therefore, future preventive or therapeutic strategies in PH and RV failure should consider combining therapies that would target multiple sites of action as previously reported. 10,18,24,55 In summary, in high-risk cardiac surgical patients, iMil has favourable hemodynamic effect, no systemic hypotension, and is associated with an increased CO with a modest overall reduction in SPAP. Reduction in RV afterload after iMil can vary amongst patients and can be explained by variable PK/PD relationships.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have shown a potential effect on the pulmonary vascular bed as well as synergistic effects with inhaled prostanoids [68,100,101]. In animal studies, milrinone decreases pulmonary artery pressure and resistance and acts additively with iNO [83,102]. Clinical reports indicate that milrinone may decrease rebound pulmonary hypertension after iNO is stopped [27], and may enhance pulmonary vasodilation of infants with PPHN refractory to iNO [103].…”
Section: Pde3 Inhibition -Milrinonementioning
confidence: 99%
“…Our experience suggests that inhaled PGI 2 is well tolerated and may assist in recovery without ECMO in infants with severe pulmonary hypertension and inadequate response to iNO [82]. Although the optimal dosing of inhaled PGI 2 in critically ill mechanically ventilated infants is not known, short-term studies in newborn lambs with pulmonary hypertension suggest that doses up to 500 ng/kg/min produce progressive improvements in PA pressure, PVR and pulmonary blood flow [83]. In our clinical experience, doses of 50–100 ng/kg/min produce rapid improvement in oxygenation in infants that are refractory to iNO [84].…”
Section: Pharmacotherapy Of Pulmonary Hypertensionmentioning
confidence: 99%